2001
DOI: 10.1093/ndt/16.9.1790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and long‐term outcome of obesity‐associated focal segmental glomerulosclerosis

Abstract: OB-FSG indicates a poor prognosis with almost one-half of patients developing advanced renal failure. Knowledge of the clinico-pathological features of this entity (obesity, FSG lesions with glomerulomegaly, absence of nephrotic syndrome despite nephrotic-range proteinuria) should be helpful in establishing an accurate and early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
203
2
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(225 citation statements)
references
References 27 publications
9
203
2
11
Order By: Relevance
“…Microalbuminuria was detected in 25 out of 207 non-diabetic obese patients in a study performed by Valensi et al 35 These findings suggest that obesityrelated renal damage should be defined as a special form of focalsegmental glomerulosclerosis slowly progressing to end-stage renal disease. 36 …”
Section: Structural Changes In the Kidneymentioning
confidence: 99%
“…Microalbuminuria was detected in 25 out of 207 non-diabetic obese patients in a study performed by Valensi et al 35 These findings suggest that obesityrelated renal damage should be defined as a special form of focalsegmental glomerulosclerosis slowly progressing to end-stage renal disease. 36 …”
Section: Structural Changes In the Kidneymentioning
confidence: 99%
“…Clinically, patients may present with the nephrotic syndrome (32), although, more often, they do not have nephrosis (27,29,30). In a series of 15 obese patients, Praga et al (30) reported the absence of features of nephrotic syndrome despite heavy proteinuria.…”
Section: Renal Structure and Function In Obesitymentioning
confidence: 99%
“…This likely occurs because of afferent arteriolar dilation as a result of proximal salt reabsorption, coupled with efferent renal arteriolar vasoconstriction as a result of elevated AngII. These effects may contribute to hyperfiltration, glomerulomegaly, and later focal glomerulosclerosis (29,30). Even though GFR is increased in obesity, urinary sodium excretion in response to a saline load is often delayed, and individuals exhibit an abnormal pressure natriuresis (135,136), indicating avid proximal tubular sodium reabsorption, likely as a result of both sympathetic activation and AngII effect.…”
Section: Other Potential Hemodynamic Factorsmentioning
confidence: 99%
“…9,10 Patients with normal numbers of nephrons may develop secondary FSGS as a result of morbid obesity, which causes an increased demand for glomerular filtration that parallels increased body mass. 11,12 Secondary forms of FSGS typically have a lower incidence of nephrotic syndrome and a better overall prognosis when compared with primary (idiopathic) FSGS. 13 Whereas the mainstay of treatment for primary FSGS is immunosuppression, secondary (postadaptive) forms of FSGS are treated with RAS blockade and treatment of the underlying cause whenever possible (e.g., weight loss in the obese patient).…”
Section: Introductionmentioning
confidence: 99%